Standardization for ovarian tissue cryopreservation and transplantation in China - Xiangyan Ruan (Gynecological Endocrinology)
Ovarian tissue cryopreservation and transplantation is one of the most advanced and promising fertility preservation methods. Prior to any procedure that may lead to a toxic ovarian injury (such as chemotherapy or radiotherapy), a portion of the ovary is removed and cryopreserved. At an appropriate time, after toxic therapy is concluded, the cryopreserved ovarian tissue is then thawed and transplanted back to the patient when conditions permit. This technique can not only preserve female fertility but also restore ovarian endocrine function. However, there is no standardization for ovarian tissue cryopreservation and transplantation in China. In order to promote the standardized development of ovarian tissue cryopreservation technology in the whole country, it is urgent to establish the standard of this technology.